2023
DOI: 10.1093/hr/uhad116
|View full text |Cite
|
Sign up to set email alerts
|

VqMAPK3/VqMAPK6, VqWRKY33, and VqNSTS3 constitute a regulatory node in enhancing resistance to powdery mildew in grapevine

Abstract: Grapevine powdery mildew is caused by Erysiphe necator that seriously harms grape production in the world. Stilbene synthase makes phytoalexins that contribute to the resistance of grapevine against powdery mildew. A novel VqNSTS3 was identified and cloned from Chinese wild Vitis quinquangularis accession Danfeng-2. Novel VqNSTS3 was transferred into susceptible ‘Thompson Seedless’ by Agrobacterium-mediated transformation. The transgenic plants showed resistance to the disease and activated other resistance-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…The results suggested that the transcript levels of a number of genes in primary and secondary metabolic pathways were higher in mlo8 CR1 , mlo11 CR1 , and mlo8 CR1 mlo11 CR1 plants relative to control after pathogen inoculation; these metabolites included the aromatic amino acid l -phenylalanine, cinnamic acid, and phenylpropanoid. A diversity of secondary metabolites function in defense against biotic stress in plants [ 42 , 43 ]. Aromatic amino acids (tryptophan, phenylalanine, and tyrosine) are the branch points where primary metabolites may enter secondary metabolic pathways that function in protecting plants from biotic stresses [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the transcript levels of a number of genes in primary and secondary metabolic pathways were higher in mlo8 CR1 , mlo11 CR1 , and mlo8 CR1 mlo11 CR1 plants relative to control after pathogen inoculation; these metabolites included the aromatic amino acid l -phenylalanine, cinnamic acid, and phenylpropanoid. A diversity of secondary metabolites function in defense against biotic stress in plants [ 42 , 43 ]. Aromatic amino acids (tryptophan, phenylalanine, and tyrosine) are the branch points where primary metabolites may enter secondary metabolic pathways that function in protecting plants from biotic stresses [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%